Successful treatment of pulmonary injury after nitrogen oxide exposure with corticosteroid therapy: A case report and review of the literature. (2017) - Kido, Yasutoshi; Mitani, Akihisa; Isago, Hideaki; Takeshima, Hideyuki; Narumoto, Osamu; Tanaka, Goh; Yamauchi, Yasuhiro; Takai, Daiya; Ohishi, Nobuya; Nagase, Takahide
Abstract: Nitrogen oxides are representative chemicals of occupational and environmental exposure, which can lead to fatal pulmonary injury. These oxides are also known to cause delayed occurrence of bronchiolitis obliterans (BO). Herein, we report a case of nitrogen oxide-induced lung injury. A 50-year-old man developed pulmonary edema after nitric acid exposure. Hypoxemia and respiratory failure were immediately improved after introduction of corticosteroid pulse therapy with supplemental oxygen. This was followed by administration of oral prednisolone, and delayed BO did not develop. This case supports the therapeutic efficacy of corticosteroids against pulmonary injury and late-onset BO after nitrogen oxide exposure. Key clinical message: Prolonged oral prednisolone might be a potential therapy to prevent delayed onset of bronchiolitis obliterans after nitric acid exposure.